Evolution of microstructure and tensile strength of rapidly solidified Al 4.7 pct Zn 2.5 pct Mg 0.2 pct Zr X wt pct Mn alloys - Chang, J; Moon, I; Choi, C (SPRINGER, 1998)
Analytical transmission electron microscopy and thermal analysis of as-extruded Al-4.7 pct Zn-2.5 pct Mg-0.2 pct Zr-X wt pct Mn alloys, with Mn contents ranging from 0.5 to 2.5 wt pct, were carried out to elucidate the microstructural change and accompanying mechanical properties during subsequent heat treatments. The as-extruded alloy was fabricated from rapidly solidified powder and consisted of a fine, metastable manganese dispersoid and the ternary eutectic T phase (Al2Mg3Zn3). Solution heat treatment resulted in the formation of the stable Al6Mn phase and complete dissolution of the T phase. Formation of stable Al6Mn was made by two routes: by phase transition from metastable Mn dispersoids which already existed, and from the supersaturated solid solution by homogeneous nucleation. The density of the Al6Mn phase increased with the addition of manganese, while the shape and average size remained unchanged. A significant increase in the hardness was observed to coincide with the formation of the Al6Mn phase. Similarly, the tensile strength increased further after the aging treatment, and the increment was constant over the content of Mn in the alloy, which was explained by the contribution from the same amount of precipitates, MgZn2. Results of thermal analysis indicated that the dissolution of the T phase started near 180 degrees C and that formation of Al6Mn occurred at about 400 degrees C, suggesting that further enhancement of strength is possible with the modification of the heat-treatment schedule.
Keywords: MANGANESE; ALUMINUM